2021
DOI: 10.1186/s12902-021-00723-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physicians’ knowledge, attitudes and concerns about bariatric surgery and the association with referral patterns: a Swedish survey study

Abstract: Background Obesity prevalence is increasing globally. Bariatric surgery is an effective treatment for severe and complex obesity resulting in significant and sustained weight loss. In Sweden, most bariatric surgery patients are referred by primary care physicians. We aimed to explore barriers for physicians to refer patients with severe and complex obesity for bariatric surgery. Methods A questionnaire survey was in 2019 emailed to 1100 primary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
2
19
1
Order By: Relevance
“…Sufficient knowledge about obesity and bariatric surgery in primary health care is an important element that might positively affect referral patterns and physicians practice. In a previous study, high knowledge was significantly correlated with better referral and positive attitude (Memarian et al, 2021). The finding of this study showed that patients who were older than 30 years and who had more than 5 years in practice demonstrated significantly better knowledge about bariatric procedures.…”
Section: Resultssupporting
confidence: 55%
“…Sufficient knowledge about obesity and bariatric surgery in primary health care is an important element that might positively affect referral patterns and physicians practice. In a previous study, high knowledge was significantly correlated with better referral and positive attitude (Memarian et al, 2021). The finding of this study showed that patients who were older than 30 years and who had more than 5 years in practice demonstrated significantly better knowledge about bariatric procedures.…”
Section: Resultssupporting
confidence: 55%
“…Currently, studies from European countries and the USA have reported that primary care physicians remain reluctant to refer their patients for bariatric/ metabolic surgery. This may be associated with a lack of knowledge [34][35][36][37]. In the results of an interview with the general public in Saudi Arabia, most participants recognized the association between obesity and its comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous publications on the safety and effectiveness of bariatric surgery in producing durable weight loss and resolving obesity-related comorbidities, its penetration in the medical community remains limited. A recent survey among Swedish PCPs has shown that half of the respondents had high concerns about postoperative complications relating to bariatric surgery and this may lead to non-referral [ 29 ]. An individual’s choice to pursue bariatric surgery may also be influenced by familial involvement and support, and cultural and/or religious beliefs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%